Viscoelastic point-of-care testing to assist with the diagnosis, management and monitoring of haemostasis: a systematic review and cost-effectiveness analysis - Whiting, Penny; Al, Maiwenn; Westwood, Marie; Ramos, Isaac Corro; Ryder, Steve; Armstrong, Nigel; Misso, Kate; Ross, Janine; Severens, Johan; Kleijnen, Jos (Health technology assessment (Winchester, England), 2015)
Patients with substantive bleeding usually require transfusion and/or (re-)operation. Red blood cell (RBC) transfusion is independently associated with a greater risk of infection, morbidity, increased hospital stay and mortality. ROTEM (ROTEM® Delta, TEM International GmbH, Munich, Germany; www.rotem.de), TEG (TEG® 5000 analyser, Haemonetics Corporation, Niles, IL, USA; www.haemonetics.com) and Sonoclot (Sonoclot® coagulation and platelet function analyser, Sienco Inc., Arvada, CO) are point-of-care viscoelastic (VE) devices that use thromboelastometry to test for haemostasis in whole blood. They have a number of proposed advantages over standard laboratory tests (SLTs): they provide a result much quicker, are able to identify what part of the clotting process is disrupted, and provide information on clot formation over time and fibrinolysis. This assessment aimed to assess the clinical effectiveness and cost-effectiveness of VE devices to assist with the diagnosis, management and monitoring of haemostasis disorders during and after cardiac surgery, trauma-induced coagulopathy and post-partum haemorrhage (PPH). Sixteen databases were searched to December 2013: MEDLINE (OvidSP), MEDLINE In-Process and Other Non-Indexed Citations and Daily Update (OvidSP), EMBASE (OvidSP), BIOSIS Previews (Web of Knowledge), Science Citation Index (SCI) (Web of Science), Conference Proceedings Citation Index (CPCI-S) (Web of Science), Cochrane Database of Systematic Reviews (CDSR), Cochrane Central Register of Controlled Trials (CENTRAL), Database of Abstracts of Reviews of Effects (DARE), Health Technology Assessment (HTA) database, Latin American and Caribbean Health Sciences Literature (LILACS), International Network of Agencies for Health Technology Assessment (INAHTA), National Institute for Health Research (NIHR) HTA programme, Aggressive Research Intelligence Facility (ARIF), Medion, and the International Prospective Register of Systematic Reviews (PROSPERO). Randomised controlled trials (RCTs) were assessed for quality using the Cochrane Risk of Bias tool. Prediction studies were assessed using QUADAS-2. For RCTs, summary relative risks (RRs) were estimated using random-effects models. Continuous data were summarised narratively. For prediction studies, the odds ratio (OR) was selected as the primary effect estimate. The health-economic analysis considered the costs and quality-adjusted life-years of ROTEM, TEG and Sonoclot compared with SLTs in cardiac surgery and trauma patients. A decision tree was used to take into account short-term complications and longer-term side effects from transfusion. The model assumed a 1-year time horizon. Thirty-one studies (39 publications) were included in the clinical effectiveness review. Eleven RCTs (n=1089) assessed VE devices in patients undergoing cardiac surgery; six assessed thromboelastography (TEG) and five assessed ROTEM. There was a significant reduction in RBC transfusion [RR 0.88, 95% confidence interval (CI) 0.80 to 0.96; six studies], platelet transfusion (RR 0.72, 95% CI 0.58 to 0.89; six studies) and fresh frozen plasma to transfusion (RR 0.47, 95% CI 0.35 to 0.65; five studies) in VE testing groups compared with control. There were no significant differences between groups in terms of other blood products transfused. Continuous data on blood product use supported these findings. Clinical outcomes did not differ significantly between groups. There were no apparent differences between ROTEM or TEG; none of the RCTs evaluated Sonoclot. There were no data on the clinical effectiveness of VE devices in trauma patients or women with PPH. VE testing was cost-saving and more effective than SLTs. For the cardiac surgery model, the cost-saving was £43 for ROTEM, £79 for TEG and £132 for Sonoclot. For the trauma population, the cost-savings owing to VE testing were more substantial, amounting to per-patient savings of £688 for ROTEM compared with SLTs, £721 for TEG, and £818 for Sonoclot. This finding was entirely dependent on material costs, which are slightly higher for ROTEM. VE testing remained cost-saving following various scenario analyses. VE testing is cost-saving and more effective than SLTs, in both patients undergoing cardiac surgery and trauma patients. However, there were no data on the clinical effectiveness of Sonoclot or of VE devices in trauma patients. This study is registered as PROSPERO CRD42013005623. The NIHR Health Technology Assessment programme.